Application of ILD2300-10 Laser Sensor on Measuring the Vertical Displacement of Fresh Concrete Surface : Technical report - Sayahi, Faez (Luleå tekniska universitet, Byggkonstruktion och brand, 2017)
Early age (< 24 h after mixing) behaviour of concrete is very critical as it may cause cracking, which eventually can dramatically influence the aesthetic, durability and serviceability of the structure. In order to have a general comprehension of the phenomenon and the governing mechanism, it is essential to measure and monitor various parameters. One of these parameters is the vertical displacement (settlement) of the concrete that can give a clue of the rheology, stiffening and approximate capillary pressure onset. After casting the concrete the solid particles of the mixture start to settle under the gravitational forces. This settlement starts immediately after placing the mixture in the mould and continues until the solid skeleton of the concrete is stiff enough to hold the weight of the particles. In such case the settlement either stops or increases with lower rate. This technical report, summarizes tests performed at Luleå University of Technology in order to evaluate the function of ILD2300-10 laser sensor (manufactured by Micro-Epsilon Snsotest AB) in measuring the settlement of fresh concrete. The laser sensor was used to measure the vertical displacement of both conventional and self-compacting concrete (SCC) cast in a mould made according to the ASTM C 1579 standard. Both mixtures had 0.67 water-cement ratio (w/c). The results show very accurate readings of the concrete settlement which clearly shows the differences of the two concrete types. Moreover, it was found that the sensor is very practical on the moist concrete and the thin water layer that covers the surface after casting does not have any significant influence on the accuracy of the measurements. However, it was noticed that the sensor is not efficient to measure the vertical displacement when airflow blows across the concrete surface. Plastic shrinkage cracking in concrete